Trace Metal Levels in Some Modern Cultivars and Turkish Landraces of Potato - Yilmaz, Gungor; Tuzen, Mustafa; Kandemir, Nejdet; Mendil, Durali; Sari, Hayati (Asian Journal of Chemistry, 2016)
Five modern and ten traditional potato varieties grown in Black Sea coastal region of Turkey were studied for copper, cadmium, manganese, zinc and iron contents. Some traditional cultivars had quite low levels of cadmium. For other minerals, in general, there were not clear differences between traditional and modern varieties. However, there were relatively high levels of variation within both groups for these minerals. The potato samples were analyzed using flame (FAAS) and graphite furnace (GFAAS) atomic absorption spectrometry after microwave digestion.